Multi-modality cardiac imaging in aorta and aortic valve from evaluation to post treatment - Suprapta, Aloysius Yuwono; Handari, Saskia Dyah (Heart Science Journal, 2025)
Aorta and aortic valve disease are crucial but usually found unintentionally while doing imaging evaluation. Genetic and non-genetical issues can be the source of the disease. Proper evaluation using multimodality of imaging can give an early diagnosis and proper treatment according to recent situation.  Aortic disease and aortic valve disease can result from genetic and non-genetic problems. Echocardiography (transthoracic or transesophageal) can be the first modality to evaluate this disease. Further modalities (computed tomography angiography, magnetic resonance imaging, and positron electromagnetic) can be used as supporting data to make more accurate analyses for diagnosis and evaluation post-treatment. Although they give more accurate images, there are some limitations in each modality. Knowing the benefits and limitations of each modality can make better use of the tools. Multimodality imaging is enhancing in detection of aortic disease and aortic valve disease. Understanding the benefits and limits of each imaging technique is essential for determining the best modality